Antinomies of modernity : essays on race, orient, nation. - Kaiwar, Vasant; Mazumdar, Sucheta éd (Globalization / postcolonialism studies., 2003)
Antinomies of Modernity asserts that concepts of race, Orient, and nation have been crucial to efforts across the world to create a sense of place, belonging, and solidarity in the midst of the radical discontinuities wrought by global capitalism. Emphasizing the continued salience at the beginning of the twenty-first century of these supposedly nineteenth-century ideas, the essays in this volume stress the importance of tracking the dynamic ways that race, Orient, and nation have been reworked and used over time and in particular geographic locations.